Separate effects of flooding and anaerobiosis on soil greenhouse gas emissions and redox sensitive biogeochemistry. Issue 4 (21st April 2014) - McNicol, Gavin; Silver, Whendee L.
Abstract Soils are large sources of atmospheric greenhouse gases, and both the magnitude and composition of soil gas emissions are strongly controlled by redox conditions. Though the effect of redox dynamics on greenhouse gas emissions has been well studied in flooded soils, less research has focused on redox dynamics without total soil inundation. For the latter, all that is required are soil conditions where the rate of oxygen (O2) consumption exceeds the rate of atmospheric replenishment. We investigated the effects of soil anaerobiosis, generated with and without flooding, on greenhouse gas emissions and redox‐sensitive biogeochemistry. We collected a Histosol from a regularly flooded peatland pasture and an Ultisol from a humid tropical forest where soil experiences frequent low redox events. We used a factorial design of flooding and anaerobic dinitrogen (N2) headspace treatments applied to replicate soil microcosms. An N2 headspace suppressed carbon dioxide (CO2) emissions by 50% in both soils. Flooding, however, led to greater anaerobic CO2 emissions from the Ultisol. Methane emissions under N2 were also significantly greater with flooding in the Ultisol. Flooding led to very low N2O emissions after an initial pulse in the Histosol, while higher emission rates were maintained in control and N2 treatments. We conclude that soil greenhouse gas emissions are sensitive to the redox effects of O2 depletion as a driver of anaerobiosis and that flooding can have additional effects independent of O2 depletion. We emphasize that changes to the soil diffusive environment under flooding impacts transport of all gases, not only O2, and changes in dissolved solute availability under flooding may lead to increased mineralization of C.